CONVERSION OF POLYETHYLENE AND RUBBER SEED SHELL MIXTURES TO SYNGAS USING CATALYTIC STEAM GASIFICATION - CHIN LAI , BRIDGID FUI (2014)
This present study investigates the behavior of co-gasification of rubber seed shells (RSS) and high density polyethylene (HOPE) waste mixtures with nickel catalyst as an alternative means of renewable energy source. The quality of the product gases are studied at different variables such as temperature of 500-900°C, RSS and HOPE particle size range of 0.125-0.625 mm and 0-40 wt% HOPE in the mixture. Furthermore, the optimum conditions to find the maximum Hz composition, CO composition and total syngas from this process is investigated using Response Surface Methodology (RSM) coupled with Central Composite Design (CCD) using the Design-Expert Version 8.0.7.1. (Stat-Ease, Inc.) software. Additionally, thermodynamic analysis, mathematical modeling for gas solid reactions and kinetic parameters are determined.